The Utilization of Audio Visual Media in Independent Curriculum to Increase Student Learning Motivation in Islamic Cultural History Course - Isnaini Rachmatul Umah; Mukhlis Fathurrohman (Bulletin of Science Education, 2024)
The purpose of this study is to examine how the use of audiovisual media in the Merdeka Curriculum can enhance student motivation in learning Islamic Cultural History in the 11th grade at MAN 2 Surakarta for the academic year 2024/2025. This research aims to boost student enthusiasm in studying Islamic Cultural History, a subject that is often perceived as less engaging. This study uses a qualitative approach with a case study method at Madrasah Aliyah Negeri 2 Surakarta. The research findings indicate that the implementation of audiovisual media at MAN 2 Surakarta significantly increased students' motivation to learn. Through the use of audiovisual media, students became more engaged and motivated, making the learning process more lively and enjoyable. In addition, audiovisual media encouraged students to think more critically about the material presented. The use of videos, animations, and multimedia presentations in the learning of Islamic Cultural History helped students understand difficult and abstract concepts in a more visual and appealing way. Overall, this study shows that audiovisual media can be an effective tool in enhancing student motivation, particularly in challenging subjects like Islamic Cultural History in the Boarding School environment at MAN 2 Surakarta